Consonant alternations in the language of Safet Sijarić's novel Rod i Dom - Mujević Dženisa (Univerzitetska Misao, 2024)
The subject of this work is the analysis of consonant changes in Safet Sijarić's novel Rod i Dom. The narrative material of this novel contains the dialectal peculiarities of the Eastern languages of Montenegro. This speech is characterized by numerous specificities that distinguish it from neighboring and other Montenegrin languages, and it is full of many interesting voice alternations, both vowel and consonant. What differentiates this speech from the neighboring ones are precisely the phonetic and phonological specificities, then the specificities of the morphological system in the context of word formation, in the context of declension, conjugation, and morphological syncretism in the case paradigm system. Dialect marks concerning consonant changes in the mentioned contexts, which are registered in the language of the novel Rod i Dom, are analyzed in detail and explained in the paper. The analysis included phenomena related to individual consonants and a detailed presentation of alternations - equalization of consonants by sonority, dissimilation of consonant groups, loss of consonants and simplification of consonant groups, iotation, and insertion of consonants.